Biochemical changes due to fungal infestation in stored seeds of some vegetable crops - B. BHADRAIAH and C. MANOHARACHARY*, G. SETHUMADHAVA RAO, S. LAXMI NARAYANA (Indian Phytopathology, 2014)
Fungi associated with seeds are known to bring about certain biochemical changes in seeds during storage and degrade seed constituents like carbohydrates, free fatty acids, amino acids, and total phenols besides bringing down the germination, plant growth and yield. The association of Aspergillus flavus, A. niger, A.Â  fumigatus, A. terreus and Cladosporium cladosporioides increased during storage period showing gradual increase with an increase in period of storage in the samples of all the leafy vegetables reaching maximum in 12th month samples. Fungal numbers, free fatty acids, total amino acids and total phenols increased with increase in storage period attaining maximum at 12 months storage. The amount of reducing sugars was observed to decrease during storage compared to post harvest.Â